Progenitors of Firm’s Search Behaviour: A Country Comparison of Australia vs. India - Ranjan Dasgupta; Monika Dhochak (Australasian Accounting, Business and Finance Journal, 2022)
The determinants and consequences of firm-risk are widely studied in regard to the US and other developed markets. However, little attention is paid to these issues in emerging markets or in cross-country contexts. The empirical literature is also mostly silent about the progenitors of firms’ search behaviour in an organisational risk context. To fill these research gaps, we investigate the progenitors of a firm’s search behaviour (i.e. risk-taking) in a bi-country context of Australia vs. India with 395 firms across 2003-2017. We use four distinctive risk measures - return on asset SD, capital expenditure ratio, accounting beta and R&D intensity, as dependent variables representing the overall search behaviour of firms and thirteen variables under four independent constructs. We use factor analysis to eliminate redundant variables and then multiple regressions to fulfil our research objectives. Results show that fundamental valuation, psychological, corporate governance and performance drivers all influence firms’ overall search behaviour. Specifically, firm size, market size, growth opportunities, board busyness, expectation, and operating and cash performance are the most critical sub-progenitors driving firm’s risk-taking. Our results are consistent across time, country-heterogeneity and industry contexts. Our study results would be of immense help to firm-managers, investors, policy-makers, and other stakeholders to assess a firm in the risk-return context from both emerging and developed country perspectives. Thereby, these would help these stakeholders in strategic policy decisions and portfolio rebalancing decisions objectively and in a timely manner.
Keywords: Firm-risk; Managerial risk-taking; Search behaviour Corporate governance; Progenitors of risk.